Handbook on Acts and Paul's Letters - Schreiner, Thomas R. 1954-; Gladd, Benjamin L. 1978- (Grand Rapids Baker Academic, 2019)
A leading biblical scholar provides an easy-to-navigate resource for studying and understanding Acts and Paul's Letters.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books